Literatura populară în lumina tiparului. Bibliofilie românească în colecţiile Bibliotecii Naţionale a României - Andreea Răsboiu (Revista de Istorie și Teorie Literară)
Being the result of a documentary research in bibliology, this paper aims to bring to light literary and bibliophilic treasures found among the first Romanian fiction books and nowadays kept within the National Library of Romania patrimony. Therefore, the National Library of Romania purpose is to ensure the unceasing existence of its valuable documents included in the national thesaurus and to perpetuate the Romanian cultural spirit through the ages. Among its collections, it can be distinguished the Romanian bibliophilia consisting in old and rare books, undoubtful evidence of the written culture in our country. Although this documentary fund covers most of all religious themes due to the local editorial activity, undertaken particularly by the clerics, still it comprises several folk literary works, in first or later editions, such as Alexandria, Esopia, Floarea darurilor, Viaţa lui Bertoldo, Halima, Pilde filosofeşti, Oglinda omului celui din lăuntru, printed in XVIII – XIX centuries. Representing successive vernacular translations and abridgments in many cases of intermediary slavic versions and not very often of the Byzantine, Italian or German original, these writings have blended in with the cultural mentality, folklore and local spirit, achieving authenticity and resemblance to the Romanian real life from that time. This bibliographic study makes reference to adventure or satirical novels, sapiential but laic books, in the same time revealing the reading priorities and practices of the period that should contribute to shaping the intellectual climate and highlight the literary taste of those centuries.